2015
DOI: 10.1016/j.juro.2015.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Fluorescence Imaging for Detection of Sentinel Lymph Nodes and Lymphatic Vessels during Open Prostatectomy using Indocyanine Green

Abstract: Intraoperative fluorescence imaging using indocyanine green during open prostatectomy enables the detection of lymphatic vessels and sentinel lymph nodes with high sensitivity. This novel method is technically feasible, safe and easy to apply with minimal additional operative time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 20 publications
3
46
1
Order By: Relevance
“…We summarised the reported findings from the different studies in Table 1 [6,7,11,13,14,26,[28][29][30][31]34,38]. In line with previous templates, most SLNs could be identified in the obturator, external/internal iliac and common iliac regions.…”
Section: Prostate Sentinel Lymph Node Detection By Anatomical Regionmentioning
confidence: 78%
See 1 more Smart Citation
“…We summarised the reported findings from the different studies in Table 1 [6,7,11,13,14,26,[28][29][30][31]34,38]. In line with previous templates, most SLNs could be identified in the obturator, external/internal iliac and common iliac regions.…”
Section: Prostate Sentinel Lymph Node Detection By Anatomical Regionmentioning
confidence: 78%
“…At high concentration, the ICG fluorophore is dark green and generates similar lymphovascular staining patterns as blue dye, which enables visual detection of superficial lymph vessels and nodes [22,25]. In pelvic SLND, ICG is diluted to a pale green solution at concentrations between 0.05mg/ml and 2.5mg/ml prior to prostatic injection [6,7,23,[26][27][28][29][30] and activated to emit near-infrared fluorescence (NIRF) by an excitation light, itself in the near-infrared (NIR) spectrum. In a prospective study comparing ICG to 99m Tc in melanoma patients, Stoffels et al demonstrated a tissue penetrance of only 10-15mm with free-ICG, preventing detection of lymphatic pathways extending to deep tissues [22].…”
Section: Fluorescence Imagingmentioning
confidence: 99%
“…It is considered that these reports apply to cases of micrometastasis. Yuen et al reported that sentinel lymph nodes were located in the obturator fossa, internal and external iliac regions, and rarely in the common iliac and presacral regions (22). There is a possibility that several LNs in the external iliac and common iliac area determined PSA recurrence.…”
Section: Standardmentioning
confidence: 99%
“…Intraprostatic free Indocyanin Green (ICG) has been utilized clinically in prostatectomy as a lymphangiographic agent in the detection of sentinel lymph nodes and for delineation of prostate by limited diffusion (9, 10). However, use of free ICG is limited by the lack of biochemical specificity to prostate or prostate cancer, and suffers from dye spillage from handling or manipulating fluorescent tissue.…”
Section: Introductionmentioning
confidence: 99%